2012
DOI: 10.1115/1.4007929
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Designing Mechatronic Systems

Abstract: Development of mechatronic products is traditionally carried out by several design experts from different design domains. Performing development of mechatronic products is thus greatly challenging. In order to tackle this, the critical challenges in mechatronics have to be well understood and well supported through applicable methods and tools. This paper aims at identifying the major challenges, by conducting a systematic and thorough survey of the most relevant research work in mechatronic design. Solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, the selection process of the ideal algorithm to find the best range of solutions needs to be done carefully. Furthermore, the designer would still need to choose one solution among a Pareto-optimal set of solutions given by the multiobjective optimization algorithm using a posteriori approaches (Wang et al , 2017; Yu et al , 2019), which is not a trivial task as reported by Torry-Smith et al (2011) and Mørkeberg Torry-Smith et al (2012). Also, the presented algorithm rejects automatically a solution that does not respect constraints.…”
Section: Resultsmentioning
confidence: 99%
“…However, the selection process of the ideal algorithm to find the best range of solutions needs to be done carefully. Furthermore, the designer would still need to choose one solution among a Pareto-optimal set of solutions given by the multiobjective optimization algorithm using a posteriori approaches (Wang et al , 2017; Yu et al , 2019), which is not a trivial task as reported by Torry-Smith et al (2011) and Mørkeberg Torry-Smith et al (2012). Also, the presented algorithm rejects automatically a solution that does not respect constraints.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mohebbi et al [5] review trends in concurrent, multi-criteria and optimal design of mechatronics systems and highlight that academic and industrial design challenges for mechatronics to a large extent also relate to conceptual and preliminary design stages. Another example is Torry-Smith et al [1,2] stating that a lack of sufficient attention to the [multi-disciplinary, auth.] dependencies causes integration problems and increased development cost [1].…”
Section: Literature Review On Sensor System Design Practicesmentioning
confidence: 99%
“…Another example is Torry-Smith et al [1,2] stating that a lack of sufficient attention to the [multi-disciplinary, auth.] dependencies causes integration problems and increased development cost [1]. One important aspect of promising design candidates is consequently the ability to achieve robust functional performance as this reflects on the quality of the final product.…”
Section: Literature Review On Sensor System Design Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing methods that would facilitate the mechatronic design process and related decision making is thus an active field of research (Chouinard et al, 2017(Chouinard et al, , 2019aMohebbi et al, 2018). The main product-related challenges associated with mechatronic devices and their multi-domain nature can be summarized as such (Torry-Smith et al, 2012):…”
Section: Mechatronicsmentioning
confidence: 99%